Leadership Leadership, School Culture and Academic Management in a Public National High School at Mayoyao National High School: An Assessment of Leadership Practices and Their Influence on School Culture and Academic Management. - Changgalan, Ginner; Martin, Matronillo (Studies in Technology and Education, 2026)
School leadership plays a critical role in shaping school culture and strengthening academic management, particularly in public national high schools operating within complex and resource-constrained environments. This study examined the leadership practices, school culture, and academic management processes at Mayoyao National High School. Using a qualitative case study design, data were gathered through semi-structured interviews with school administrators and teachers, classroom observations, and document analysis of academic plans and supervisory records. Thematic analysis revealed three interrelated domains: leadership practices that emphasize instructional and relational leadership, school culture characterized by collaboration and shared accountability, and academic management systems focused on curriculum alignment, monitoring of learner performance, and teacher support. Findings indicate that effective leadership fosters a positive school culture that supports coherent academic management and instructional improvement. The study underscores the importance of leadership that integrates instructional focus, cultural responsiveness, and systematic academic management to enhance teaching and learning in public secondary schools.